Heaviness, space and journey – innovation opportunities and restrictions. Issue 2 (2nd May 2018) - Håkansson, Håkan; Waluszewski, Alexandra
Abstract : Purpose: The purpose of this paper is to argue that if the authors want to understand the role of heaviness, space and journey in innovation, the authors have to start with the interaction itself, that is the exchange process taking place between economic actors. Three major aspects will be considered: the first is that heaviness, space and journey imply restrictions, the second is that these aspects can be positively utilised in innovation processes, and the third is their joint importance to contemporary policy. All innovation processes must bypass and build on existing investments in social and material resources, related across time and space. Design/methodology/approach: The theoretical foundation is a basic IMP observation: exchange has a content. Exchange is captured as an interaction process that creates specific imprints on material and social resources involved – across firm boundaries, and across time and space. The methodology is a consequence of the research question and the theoretical point of departure and is based on three earlier IMP studies, where heaviness has been measured in different ways. The authors utilize two earlier presented case studies to focus on the heaviness, space and journey dimensions. Findings: Three main aspects are discussed: the first aspect concerns the need for utilisation of others heaviness in order for the innovation to gain heaviness in itself. The second aspect concerns the consequences that the search for heaviness has for the creation of an innovation space. The third aspect concerns the innovation journey; the specific interaction patterns between significant actors as well as places hosting heavy using, producing and developing activities created through interactions over time. Research limitations/implications: In order to change or to establish a new economic exchange interface, there is an urgent need to be aware of and utilise heaviness, to find out in what way existing investments made in related interfaces can be taken advantage of. In order to do that, there is a need for a better understanding of the function of heaviness, spatial and journey aspects included. Practical implications: In contemporary policy, certain heaviness is recognised, however, only in a non-business developing setting. The first conclusion is that heaviness of established producing and using settings is a policy blind spot. This implies that analytical policy approaches are not equipped for recognitions or of estimations of heaviness, nor as a hindrance or as a possibility in producing and using settings. The second conclusion is that the policy definition of the role of place implies neglecting the innovation space. The third conclusion is that there is a need for policy to recognise the innovation journey and its consequences. Social implications: If the policy is expected to have regional effects, policy analysis has to start out from the established heaviness of the region and consider how it can be taken advantage of. Originality/value: The paper draws attention to an aspect neglected in policy attempts to boost innovation, that the mobilising support has to come from actors representing heavy producing and using networks – and that these already have space and journey characteristics. A peripheral actor can come up with a suggestion for change – but it cannot alone mobilise the resources necessary for an innovation to get a space and journey in relation to established resource constellations.